If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2k + -6k = 0 Combine like terms: -2k + -6k = -8k -8k = 0 Solving -8k = 0 Solving for variable 'k'. Move all terms containing k to the left, all other terms to the right. Divide each side by '-8'. k = 0 Simplifying k = 0
| 14x+44=12-9x | | 3y-(-8)=50 | | 4w-9=5 | | 2m-2-5m= | | 8x-7=5x-13 | | 11y-24=3y | | -70-20x=-45-8x | | f(x)=x^2-12+42 | | 7(y-3)=4y-29 | | 2x+50=70 | | 4-2(x+3)=-7x+(-2) | | 6x-3+2=8x+7-10 | | -88=5(-2x-8)-6x | | 8s=96 | | x+2(2x+3)-1=0.5(4x+28) | | -2b+5-3+b=b-4b+1-10 | | 2r-4r=4-r | | 5x+40=2 | | -(k-3)+3k=-25+6k | | 4a-12=2a+6 | | 1-3x^2-4x^3=0 | | 470+2x=330+4x | | 18x+27y=10 | | -7(3x+6)+x=-6x-4(6x+8) | | 7(x+10)=140 | | x/2-8.5=15 | | f(x)=-6+3x | | 3x-7=72 | | (x+2)-(-3x-8)= | | 24x^2+20x-24= | | -16+2d=5+4d | | 3x^2-265=3x^2-10x+6.25 |